STIP review of Lesotho : an implementation strategy - Masin, Menelea (UN New YorkUS, 2010)
Analyses key STI resources. Guides policymakers, researchers, decision-makers and civil society toward a number of mechanism that can facilitate action. Outlines a structure to proactively coordinate cross-sectoral action, priority setting and fund allocation.